Österreich im Kalten Krieg Neue Forschungen im internationalen Kontext - Graf, Maximilian; Meisinger, Agnes (Zeitgeschichte im Kontext, 2016)
Austria's international position in the Cold War is eversince a subject to controversial debates. This volume presents the current state of research and highlights existing desiderata. The various chapters on recent questions of Cold War History – all of them written by young historians – are well embedded into current international debates. The volume delivers new insights into the relatively well researched occupation period (1945–55), provides articles adressing international perceptions of neutral Austria, and, moreover, it offers fresh studies on the Austrian Cold War theatre with regard to the multidimensional nucelar age, transnational cultural interactions, and state representations in the very same field throughout the whole Cold War era.; Die Beiträge des Bandes liefern wichtige Ergänzungen zum relativ gut erforschten Besatzungsjahrzehnt (1945–55), greifen neue Themen auf und sind um eine Einbettung der Untersuchungen zu Österreich in internationale Forschungsdebatten bemüht. Neben Fragen der internationalen Perzeption der Politik Österreichs greift der Band insbesondere rezente Fragestellungen auf, etwa die vieldimensionale atomare Herausforderung, kulturelle transnationale Interaktionen und staatliche Repräsentationen in diesem Feld. Die ausgewogenen und fundierten Analysen beleuchten viele bisher nur wenig bekannte Aspekte, relativieren bisher tradierte Mythen und zeigen auf, wie wünschenswert neue Forschungen zu Österreich im Kalten Krieg sind